UDP-4-Keto-6-Deoxyglucose, a Transient Antifungal Metabolite, Weakens the Fungal Cell Wall Partly by Inhibition of UDP-Galactopyranose Mutase - Ma, Liang (mBio, 2017)
Can accumulation of a normally transient metabolite affect fungal biology? UDP-4-keto-6-deoxyglucose (UDP-KDG) represents an intermediate stage in conversion of UDP-glucose to UDP-rhamnose. Normally, UDP-KDG is not detected in living cells, because it is quickly converted to UDP-rhamnose by the enzyme UDP-4-keto-6-deoxyglucose-3,5-epimerase/-4-reductase (ER). We previously found that deletion of the er gene in Botrytis cinerea resulted in accumulation of UDP-KDG to levels that were toxic to the fungus due to destabilization of the cell wall. Here we show that these negative effects are at least partly due to inhibition by UDP-KDG of the enzyme UDP-galactopyranose mutase (UGM), which reversibly converts UDP-galactopyranose (UDP-Galp) to UDP-galactofuranose (UDP-Galf). An enzymatic activity assay showed that UDP-KDG inhibits the B. cinerea UGM enzyme with a K(i) of 221.9 µM. Deletion of the ugm gene resulted in strains with weakened cell walls and phenotypes that were similar to those of the er deletion strain, which accumulates UDP-KDG. Galf residue levels were completely abolished in the Δugm strain and reduced in the Δer strain, while overexpression of the ugm gene in the background of a Δer strain restored Galf levels and alleviated the phenotypes. Collectively, our results show that the antifungal activity of UDP-KDG is due to inhibition of UGM and possibly other nucleotide sugar-modifying enzymes and that the rhamnose metabolic pathway serves as a shunt that prevents accumulation of UDP-KDG to toxic levels. These findings, together with the fact that there is no Galf in mammals, support the possibility of developing UDP-KDG or its derivatives as antifungal drugs.